Selecting differentially expressed genes for colon tumor classification - Fujarewicz, Krzysztof; Wiench, Małgorzata (Zielona Góra: Uniwersytet Zielonogórski)
DNA microarrays provide a new technique of measuring gene expression, which has attracted a lot of research interest in recent years. It was suggested that gene expression data from microarrays (biochips) can be employed in many biomedical areas, e.g., in cancer classification.
Keywords: colon tumor; gene expression data; microarrays; support vector machines; feature selection; classification